Analisis Karakteristik Perilaku Manusia Konteks Kitab Targhib Wa Tarhib As-Syeikh Husein (Hafidz Al-Mundziri) - Novira Arafah; Sarini Musyafi’ah Ali; Samsul Hadi (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2021)
This study was conducted to describe and measure: (1) Characteristics of human behavior (2) Behavior based on the concept of the book Targhib wa Tarhib As-Syeikh Husein. The type of research used is descriptive qualitative is literature study. The results of this study indicate: (1) The characteristics of human behavior indicate a variety of human behavior. This diversity depends on how it is managed. In this case, of course, humans as the center of the center (2) Characteristics of human behavior in the context of Targhib wa Tarhib is to explain the Islamic concept of how behavior can refer to the direction of reward and punishment. Does something deserve appreciation or refers to the negligence that caused the punishment to be given. In this way, the Islamic concept also recognizes that praiseworthy behavior can be imitated, so that it is entitled to praise, praise and appreciation, while on the contrary, it is the same.